2020
DOI: 10.3389/fphar.2020.584956
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Treatment of Coronavirus Disease 2019 (COVID-19): Therapeutic Repurposing and Unmet Clinical Needs

Abstract: For the initial phase of pandemic of coronavirus disease 2019 (COVID-19), repurposing drugs that in vitro inhibit severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) have been attempted with overlooked or overestimated efficacy owing to limited clinical evidence. Most early clinical trials have the defects of study design, small sample size, non-randomized design, or different timings of treatment initiation. However, well-designed studies on asymptomatic or mild, or pediatric cases of COVID-19 are sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 84 publications
(103 reference statements)
0
34
0
Order By: Relevance
“…The COVID-19 pandemic has far reaching direct and indirect medical and social consequences. So far, there is still an unmet clinical need in defining patient prognosis and effective therapeutic approaches ( 17 ). Several parameters have been proposed to define COVID-19 patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has far reaching direct and indirect medical and social consequences. So far, there is still an unmet clinical need in defining patient prognosis and effective therapeutic approaches ( 17 ). Several parameters have been proposed to define COVID-19 patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the prolonged pandemic process and the lack of a suitable treatment as of yet, the drug repurposing approach comes to the fore (Table 1). The fact that the side effects of the drugs used in this approach are known and clinical studies and regulation studies have been conducted provide rapid results [141][142][143][144]. Each of the drugs used in the treatment are effective at different stages of the virus's life cycle.…”
Section: Therapeutics For Covid-19 Treatmentmentioning
confidence: 99%
“…It is the phosphorylated metabolite that delivers potent antiviral activity through distinct but related mechanisms (Fig. 2 ): (A) interfering with the action of viral RNA-dependent RNA polymerase (RdRp); (B) evading exoribonuclease-proofreading; and (C) causing delayed/cyano-group mediated chain termination of viral genome (Chen et al 2020 ; Malin et al 2020 ; Ottoni et al 2020 ; Singh et al 2020 ; Tchesnokov et al 2019 ; Yin et al 2020 ). We have shown that human carboxylesterase-1 (CES1), a highly efficient enzyme, was involved in the hydrolytic activation of remdesivir (Shen et al 2021a , b ).…”
Section: Overview Of Remdesivirmentioning
confidence: 99%